Tracking coarse sediment in an Alpine subglacial channel using radio-tagged particles - Jenkin, Matt; Hofmann, Margaux; Hubbard, Bryn; Mancini, Davide; Miesen, Floreana M.; Herman, Frédéric; Lane, Stuart N. (Journal of Glaciology, 2023)
We present a method for tracking radio-tagged pebbles and cobbles through subglacial meltwater channels under shallow temperate glaciers. Natural particles tagged with active radio transmitters were injected directly into a large subglacial channel 300 m up-glacier from the terminus of the Glacier d'Otemma, Switzerland. A roving antenna was developed to localise tagged particles planimetrically in subglacial and proglacial channel reaches (350 and 150 m long, respectively) using a probabilistic technique, delivering records of the change in particle location and transport distance over time with uncertainty. The roving antenna had a ±5−15 m planimetric precision, a 75% particle localisation rate and operated at a maximum ice depth of 47 m. Additionally, stationary supraglacial and proglacial antennas continuously monitored the passage of tagged particles through consecutive reaches of the channel, constraining the timing of particle transport events. The proglacial antenna system had a 98.1% detection rate and was operational to 0.89 m water depth during testing. Roving and stationary antenna records were combined to create a transport distance model for each particle, which may be used in conjunction with hydraulic data to investigate the kinematics of particle motion. When applied at scale in future studies, this method may be used to reveal the mechanisms and timescales of coarse sediment export from Alpine glaciers.